Effects of lacticaseibacillus paracasei shirota supplementation on growth performance, intestinal health, and fecal AFB metabolite in AFB1-exposed rats - Muhammad Firdhaus Shaharudin,; Siti Raihanah Shafie,; Mohd Redzwan Sabran,; Maizaton Atmadini Abdullah,; Fauzah Abd Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Aflatoxin B1 (AFB1) is a toxin produced by Aspergillus species of fungi. Findings in the literature has shown the potential of probiotic treatment to alleviate AFB1 toxicity. This study explores the effects of Lacticaseibacillus paracasei Shirota (LcS) supplementation on the growth performance, intestinal health, and excretion of faecal AFB1 metabolite of AFB1- exposed rats. Thirty-two male Sprague Dawley rats were divided into control, AFB1, AFB1+LcS and LcS groups. AFB1 was given at a complete dosage of 25 µg AFB1/kg body weight, while LcS supplementation at 2×109 CFU/mL per day for four weeks. The average body weight of the AFB1 group showed no significant increase from week 2 to 4, while other groups had an increment throughout the study. The food intake of the AFB1 and AFB1+LcS groups had significantly reduced throughout the treatment period. AFB1 exposure caused several changes in the histomorphometry parameters but was normalised with LcS supplementation. The AFB1 group showed mild to moderate inflammation in all intestinal parts, whereas only mild inflammation was observed in the jejunum and ileum of the AFB1+LcS group. Faecal Bifidobacterium spp. counts showed an increment in three groups, while the AFB1 group showed a significant reduction. The faecal AFB1 in the AFB1 group was significantly lower than in the AFB1+LcS group. In conclusion, AFB1 affected growth performance and intestinal health, and wherein the effects were alleviated by LcS supplementation. Further investigation on intestinal permeability and serum and urinary AFB1 level is suggested to understand the mechanism of probiotic-AFB1 interaction in alleviating AFB1 toxicity.